Combined label-free optical and optoacoustic imaging of model organisms at mesoscopy and microscopy resolutions - Soliman, Dominik; Tserevelakis, George J.; Omar, Murad; Ntziachristos, Vasilis (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2016)
We present a multi-scale imaging system that integrates five optoacoustic and multi-photon modalities into the same device. The hybrid microscope offers a unique zoom-in ability by allowing for optoacoustic microscopy and mesoscopy scans of the sample within the same imaging framework. Furthermore, by combining several label-free modalities, we are able to visualize a broad range of anatomical features, taking advantage of their complementary contrast mechanisms. We characterize the spatial resolution and relative orientation of the different sub-modalities and demonstrate the system's performance by the imaging of several model organisms ex vivo. The presented ability to dynamically vary scanning volume and resolution together with its multi-contrast and label-free imaging capabilities make the hybrid microscope a promising tool for comprehensive biological imaging.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Mesoscopy; Multi-modal imaging; Multi-scale imaging; Multiphoton microscopy; Optoacoustic microscopy; Photoacoustic microscopy